HUBUNGAN ANTARA PERSEPSI TERHADAP IKLIM KELAS DENGAN MOTIVASI BELAJAR SISWA SMP NEGERI 1 BANCAK - Puspitasari, Devi Brantaningtyas (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
Abstract This study aimed is to determine the relationship between perceptions of classroom climate with student motivation. The samples in this study come from the eighth grade students from SMP Negeri 1 Bancak. Cluster random sampling technique is used in this study. Perceptions of classroom climate scale and learning motivation scale was used to collect the data. The data obtained were further analyzed by using Pearson product moment correlation technique. The result of analysis showed that there is no relationship between the perception of class climate with motivation to learn among student (r = - .0.194; p 0.118). The results of this study stated that the hypothesis is rejected. There is no relationship between perceptions of classroom climate and motivation to learn. Keywords: perceptions of classroom climate, learning motivation.